Identification of SETD4 as an Onco‐Immunological Biomarker Encompassing the Tumor Microenvironment, Prognoses, and Therapeutic Responses in Various Human Cancers - Yuyun Zhong; Ruiqi Wang; Zijie Huang; Zhaoting Hu; Bin Peng; Bin Chen; Liyue Sun (Immunity, Inflammation and Disease)
ABSTRACT Background SET domain‐containing protein 4 (SETD4) is a histone methyltransferase that has been shown to modulate cell proliferation, differentiation, and inflammatory responses by regulating histone H4 trimethylation (H4K20me3). Previous reports have demonstrated its function in the quiescence of cancer stem cells as well as drug resistance in several cancers. A limited number of systematic studies have examined SETD4's role in the tumor microenvironment, pathogenesis, prognosis, and therapeutic response. Methods Utilizing The Cancer Genome Atlas database, and other publicly accessible platforms, we comprehensively analyzed SETD4 gene expression, methylation patterns, and prognostic significance. Furthermore, we investigated its association with cancer‐related pathways, the immune microenvironment, immunotherapy markers, and drug resistance signatures of chemotherapy. Additionally, qRT‐PCR was performed to validate SETD4 expression in clinical specimens. Results The expression of SETD4 was abnormal across a variety of cancer types and the expression of SETD4 in colorectal cancer tissues was verified in clinical specimens. The upregulation of SETD4 may be a prognostic risk factor predicting poor overall survival and progression‐free survival. The analysis revealed that the mRNA level of SETD4 was modulated by promoter methylation, and patients with lower methylation levels showed shorter survival times. Pathway analysis showed that SETD4 influenced several key cell cycle pathways, including the G2M checkpoint, and mitotic spindle pathways. In addition, SETD4 negatively affects immune cell infiltration in most cancers, including B cells, CD8 T cells, and macrophages. The correlation between SETD4 and cancer stemness as well as homologous recombination deficiency varied across tumor types, suggesting that SETD4 may play a multifaceted role in tumor resistance. Notably, we identified several potential agents targeting SETD4. Conclusions This study demonstrates that SETD4 is an immune‐oncogenic molecule in multiple cancers, with the potential to be a diagnosis, prognosis, and targeted therapy marker.